A distributed and integrated control strategy for an islanded microgrid considering line loss and communication interruption. (October 2022) - Yuan, Dongmei; Lu, Zhigang; Zhang, Jiangfeng; Guo, Xiaoqiang; Geng, Lijun
Abstract: To improve the stability and economic operation performance of multi-distributed energy resources in networked islanded microgrid, a distributed and integrated control strategy is designed in this study. The strategy is based on the communication network in an islanded microgrid, which is able to achieve minimal generation cost, reliable communication, and stable voltage and frequency. These targets are achieved through the following methods. Firstly, a power regulation part is combined with droop controller to constitute an improved primary control, which can take the line loss factor into account and adjust the output power of each distributed energy resource to its optimal value. Secondly, an optimal path reconstruction method and a Kalman filter estimation method with sliding mode controller are developed to address the communication interruption problem in communication channels and output channels, respectively. In the end, the secondary controller is used to regulate voltage and frequency, and a small signal model method is applied to analyze the impact on the whole system when these designs are applied. The effect of the proposed strategies has been verified by the related case studies. Highlights: Improved primary control is proposed to reduce the generation cost of microgrid. Power regulation part can make controllable DERs output optimal power quickly. Two kinds of Interruption problems among communication devices are addressed. SC is proposed to ensure voltages and frequency output by DERs stable. Small signal mode method is used to analyze the operation stability.